The Human Papillomavirus Enigma: A Narrative Review of Global Variations in Oropharyngeal Cancer Epidemiology and Prognosis - Hitesh Rajendra Singhavi; Pankaj Chaturvedi; Deepa Nair (Indian Journal of Public Health)
Oropharyngeal cancers (OPCs) in Asia account for 42% of the global burden and over 50% of related deaths. Human papillomavirus (HPV) is involved in over 70% of OPC cases in the Western hemisphere, but its role in the Eastern hemisphere is unclear. This study reviews OPC epidemiology, including prevalence, etiological factors (such as smokeless tobacco and HPV), and their interaction. Among the SEAR countries, India had the highest incidence of HPV-related OPCs at 38.4%, while data were unavailable for most African countries, with only a 14% incidence reported. Conversely, the American region exhibited one of the highest HPV positivity rates, reaching up to 65% in different states of the USA, while Brazil reported an incidence of up to 38%. In the European Union, the UK had the highest incidence of HPV-associated OPC, reaching up to 52%. In the Western Pacific region, New Zealand demonstrated the highest incidence at up to 78%. Smokeless tobacco consumption was higher in SEAR countries, which had a relatively lower incidence of HPV infection, suggesting a negative correlation between the two. Based on our literature search, the most common detection methods used globally are immunohistochemistry for p16 and polymerized chain reaction. OPCs are a global health concern, and proper identification and classification are vital. HPV-driven cancers have better survival rates, emphasizing the need for focused research on specific problem areas based on the burden of HPV-positive or HPV-negative cancers.